Głosy uwięzione w zielnikach. Zapomniane badaczki flory litewskiej w XX wieku - Kita, Jarosław; Korybut-Marciniak, Maria; Agnieszka Gralak (W zwierciadle rzeczy, 2022)
The development of natural sciences in the nineteenth century resulted in creation of numerous botanical collections and the accumulation of herbarium collections in university centers at the established natural history and in the center’s societies. An important assessment is that women, until the 1860s, were unable to obtain higher education, and thus also to conduct independent research and publication of their results, women played a significant role in the development of botanical sciences. The article gives a closer look at portraits of Polish women from Kresy, authors of herbariums, forgotten female researchers of the flora of Lithuanian-Belarusian lands in the 19th century: Maria Twardowska of Skirmunt (1857–1907) and Tekla Symonowiczówna (1838–1900).